If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -2) = 2(x + -2) Reorder the terms: 4(-2 + x) = 2(x + -2) (-2 * 4 + x * 4) = 2(x + -2) (-8 + 4x) = 2(x + -2) Reorder the terms: -8 + 4x = 2(-2 + x) -8 + 4x = (-2 * 2 + x * 2) -8 + 4x = (-4 + 2x) Solving -8 + 4x = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -8 + 4x + -2x = -4 + 2x + -2x Combine like terms: 4x + -2x = 2x -8 + 2x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 -8 + 2x = -4 + 0 -8 + 2x = -4 Add '8' to each side of the equation. -8 + 8 + 2x = -4 + 8 Combine like terms: -8 + 8 = 0 0 + 2x = -4 + 8 2x = -4 + 8 Combine like terms: -4 + 8 = 4 2x = 4 Divide each side by '2'. x = 2 Simplifying x = 2
| 21=9x+3 | | 33y=8(4y-6) | | 16n+4n+4n-5n-18n=11 | | g^2-32g+256=0 | | 5/4m=7/12 | | -2y+6(y-8)=-28 | | 9x-4=4x+5 | | 250=50+25h | | 6x^3-864x=0 | | A+17=104 | | 7t-t-2t-3t=1 | | 63(6x)-63(2x)=63 | | w*2=36-5 | | z^2+(7-7i)z+(2-26i)=0 | | 18r+r+r-14r-4r=-20 | | 3(-13+4y)+7y=29 | | 750=400+49g | | M-1/4=8/9 | | 13.2=-16x^2+24t+16.4 | | 28(6x)-28(2x)=28 | | x^2+y^2+2xy+1=0 | | 81=6-4x | | 3x^2+6x=42 | | 3x^4-30x^3+75x^2=0 | | -.02=-1.2 | | 4x+2x+3=10x+3 | | 25.6=16(t) | | x+y+67=d | | e^(19/x) | | 16=25.6(t) | | 17.92(7)=d | | d-6.12=8 |